Prevalence of Diabetes Mellitus in the School: A Systematic Review of African Studies (Global Journal of Medical Research, 2022)
Introduction: Diabetes Mellitus (DM) is a metabolic disorder which results in increased glucose level in the blood. When poorly managed it results in morbidity, mortality and low quality of life among patients. The rising prevalence of DM among teachers and students in Africa is becoming disturbing. The authors systematically reviewed studies reporting the prevalence of DM among teachers and students in Africa. Materials and Methods: We searched Pubmed, Google Scholar, Medline, Scopus, African Journal Online, Science Direct, and the Cochrane Library. Using MeSH headings, such as #x2018;#x2018;diabetes mellitus,#x2019;#x2019; #x2018;#x2018;prevalence,#x2019;#x2019; #x201C;primary,#x201D; #x201C;secondary#x201D; students,#x201D; #x201C;teachers,#x201D; #x201C;educator,#x201D; #x201C;instructor,#x201D; and #x2018;#x2018;Africa#x2019;#x2019; from year 1990 to 2019. Studies included in the systematic review were those that were conducted in primary and secondary schools and utilized the fasting blood sugar (FBS), and the random blood sugar (RBS) test.
Keywords: diabetes mellitus; prevalence; school; primary; secondary; Africa